2005
DOI: 10.1038/nmeth843
|View full text |Cite
|
Sign up to set email alerts
|

In situ detection of miRNAs in animal embryos using LNA-modified oligonucleotide probes

Abstract: MicroRNAs (miRNAs) are 20-23 nucleotide (nt) RNA molecules that regulate gene expression post-transcriptionally. A key step toward understanding the function of the hundreds of miRNAs identified in animals is to determine their expression during development. Here we performed a detailed analysis of conditions for in situ detection of miRNAs in the zebrafish embryo using locked nucleic acid (LNA)-modified DNA probes and report expression patterns for 15 miRNAs in the mouse embryo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
422
2
6

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 564 publications
(450 citation statements)
references
References 12 publications
20
422
2
6
Order By: Relevance
“…This analysis should allow us to follow miRNA expression profiles within epithelial cells that are differently stimulated. Alternatively, it was recently described that locked nucleic acid (LNA)-modified DNA probes could be used to follow the miRNA expression profile in mouse embryos by in situ hybridisation [29]. Such a strategy could reveal the precise location of miRNA within the mammary tissue at various developmental stages.…”
Section: Mirna Expression In Mammary Epithelial Cellsmentioning
confidence: 99%
“…This analysis should allow us to follow miRNA expression profiles within epithelial cells that are differently stimulated. Alternatively, it was recently described that locked nucleic acid (LNA)-modified DNA probes could be used to follow the miRNA expression profile in mouse embryos by in situ hybridisation [29]. Such a strategy could reveal the precise location of miRNA within the mammary tissue at various developmental stages.…”
Section: Mirna Expression In Mammary Epithelial Cellsmentioning
confidence: 99%
“…Although powerful, this method requires transgenic animals to visualize expression in vivo. Recently, it has been reported that nonradioactive in situ hybridization with locked nucleic acid (LNA) probes labeled with a digoxigenin hapten can be used to detect miRNAs (Sokol and Ambros, 2005;Wienholds et al, 2005;Kloosterman et al, 2006;Nelson et al, 2006). We have independently developed an in situ hybridization method for miRNA detection based on RNA oligonucleotide probes linked to a fluorescein hapten.…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances have shown that miRNA expression during development is highly tissue-specific (9)(10)(11)(12), which suggests that miRNA may be involved in specifying and maintaining tissue identity. For example, the expression of miR-124a is restricted to the brain and spinal cord in the fish and the mouse, and to the ventral nerve cord in the fly (13).…”
mentioning
confidence: 99%